2013-{2012-1·[2011-a·(2010+2013:2013)+2011]}=1
Răspunsuri la întrebare
Răspuns de
7
2013-{2012-1•[2011-a•(2010+2013:2013)+2011]}=1
2013-{2012-1[2011-a•(2010+1)+2011]}=1
2013-{2012-1•[2011-a•2011]}=1
2012-1•[2011-a•2011]=2013-1=2012
1•[2011-a•2011]=0
2011-a•2011=0
a=1
sper că te-am ajutat!!!!
2013-{2012-1[2011-a•(2010+1)+2011]}=1
2013-{2012-1•[2011-a•2011]}=1
2012-1•[2011-a•2011]=2013-1=2012
1•[2011-a•2011]=0
2011-a•2011=0
a=1
sper că te-am ajutat!!!!
xstef:
Multumesc
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Spaniola,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă